Sistem Informasi Geografis Pencarian Rute Optimum Lokasi Obyek Wisata Kota Semarang Menggunakan Algoritma Dijkstra - Bambang Agus Herlambang; Septio Oggy Pradana; Rahmat Robi Waliyansyah (Journal of Applied Science and Technology, 2022)
The Semarang City Government is currently developing tourism potential in the Semarang City area. However, the number of tourist attractions in the city of Semarang makes tourists who come to the city of Semarang to be confused to visit the tourist attractions that will be visited. In this study the authors provide solutions for grouping based on the type of tour such as religious tourism, environmental tourism, water tourism, nature tourism and education tourism. The use of the Dijkstra algorithm will be used to help find solutions to visit these tourist attractions. In this system the Google Maps API will be used to display spatial data to indicate the route to be passed. System design to create a Geographic Information System using the Unified Modeling Language (UML). Tourists later use this application by entering the initial location information and the location you want to get to get the route. Based on testing that has been done the system is able to display information on the route it travels will be bypassed by tourists. The results of research and field studies that have been carried out, can be concluded from the user acceptance testing in terms of usefulness of 89.5%, in terms of use of 89.3%, in terms of appearance of 89.5%, and in terms of accuracy of 87.6%, that is strongly agree.